Feedback Control Variables Have No Influence on the Permanence of a Discrete n-Species Schoener Competition System with Time Delays - Qianqian Su; Na Zhang (Discrete Dynamics in Nature and Society)
We consider a discrete n-species Schoener competition system with time delays and feedback controls. By using difference inequality theory, a set of conditions which guarantee the permanence of system is obtained. The results indicate that feedback control variables have no influence on the persistent property of the system. Numerical simulations show the feasibility of our results.